Constraints in Authoring BIM Components for Optimal Data Reuse and Interoperability: Results of Some Initial Tests - Lockley, S.; Greenwood, D.; Matthews, Jane; Benghi, C. (IGI Global, 2013)
This research investigates the issues of authoring reusable BIM components that can be delivered across multiple platforms. A key constraint in the uptake of Building Information Modelling (BIM) technology is interoperability, the ability to accurately and automatically share and exchange data. This has been addressed by the creation of a system of standards; Industry Foundation Classes (Ifcs). Recognising the importance of Ifc standards, the promoters of many proprietary BIM software platforms generally claim that their products support them fully. This has been challenged, and the reported work has aimed to test these assertions. A simple test model was constructed to represent the various geometries that are encountered, which were then expressed in Ifc files. Fourteen commonly-used BIM software tools were subjected to tests in which the range of geometries within the test model was imported into each tool in Ifc format. A simple visual analysis of the outcomes showed a dramatic failure to process the geometries as they were intended. The results of the study indicate that the current commercial BIM authoring tools, whilst being technically capable of providing support for the required component geometric representations, are constrained from doing so by their conversion interfaces from Ifc geometries. The practical implications of this are considerable, and could result in the possibility of serious errors within designs for construction projects. This is particularly relevant in the case of the BIM library components that are currently being authored for importing into project design models. The test model has been circulated to experts in the area, and their observations, as well as results of any further tests will be made publicly available.